The Terrible Two get worse - Barnett, Mac 1982-; John, Jory (Amulet Books, 2016)
"Friends and pranking partners Miles and Niles face a tough challenge when their favorite goat and nemesis, Principal Barkin, is replaced by his stern, no-nonsense father, Principal Barkin Senior, who turns the school into boot camp"...
Keywords: Practical jokes; Tricks; School principals; Schools; Friendship; Humorous stories; Jugendbuch; Kinderbuch